The impact of peripheral nerve blocks on perioperative outcome in hip and knee arthroplasty—a population-based study. Issue 10 (October 2016) - Memtsoudis, Stavros G.; Poeran, Jashvant; Cozowicz, Crispiana; Zubizarreta, Nicole; Ozbek, Umut; Mazumdar, Madhu
Abstract : Abstract: The role of anesthesia techniques on perioperative outcomes on a population level has recently gained widespread interest. Although mainly neuraxial vs general anesthesia has been addressed, population-level data on the impact of peripheral nerve blocks (PNBs) are still lacking. Therefore, we investigated the association between PNB use and outcomes using retrospective data on 1, 062, 152 recipients of hip and knee arthroplasties (total hip arthroplasty [THA]/total knee arthroplasty [TKA]) from the national Premier Perspective database (2006-2013). Multilevel multivariable logistic regression models measured associations between PNB use and outcomes. Complications included cardiac, pulmonary, gastrointestinal and renal complications, cerebrovascular events, infections, wound complications, thromboembolic complications, inpatient falls, and mortality. Resource utilization variables included blood transfusions, intensive care unit admissions, opioid consumption, cost, and length of stay. Overall, 12.5% of patients received a PNB, with an increase over time particularly among TKAs. Peripheral nerve block use was associated with lower odds for most adverse outcomes mainly among patients with THA. Notable beneficial effects were seen for wound complications (odds ratio 0.60 [95% confidence interval, 0.49-0.74]) among THA recipients and pulmonary complications (odds ratio 0.83 [95% confidence interval, 0.72-0.94]) in patients with TKA. Peripheral nerve block use was significantly ( P < 0.0001) associated with a −16.2% and −12.7% reduction in opioid consumption for patients with THA and TKA, respectively. In conclusion, our results indicate that PNBs might be associated with superior perioperative population-level outcomes. In light of the inability to establish a causal relationship and the presence of residual confounding, we strongly advocate for further prospective investigation, ideally in multicenter, randomized trials, to establish the potential impact of PNBs on outcomes on a population level. Abstract : Supplemental Digital Content is Available in the Text.In over 1 million orthopedic surgeries, peripheral nerve blocks were associated with beneficial outcomes, calling for further research to establish causality to support a broader utilization with potential benefits.